STUDY OF IRRIGATION CHANNEL POLLUTION FROM LEACHATE BASED ON COD AND CHROMIUM WITH MATHEMATICAL MODELING (CASE STUDY: FORMER CICABE WASTE DISPOSAL) - Try Julita Sembiring, Elsa
17~eleochaJe generated from final disposal thor still active and iiUJctive, is potentially to pollute environrment as long it contaCJs with the water. Cicabe waste disposal site was one of final disposal site that had been inactive since 2006 in the Mandalajati Village, Bandung. This research was conduc:ted in the irrigation channel that acrossed next to Cicabe former waste disposal site to Cisanggarung River. Pollutant porameter studied were COD and Chromium (Cr) . To determine the pol/want trasnport along the stream, it was used the equation of I -dimensional analytical model based on advection - dispersinn and plug flow equation in the water surface. The sampling was done twice for model calibraJicm and validation need. The samples collected included soil, sediment, and water. Pollutant input generated from leachete, clomestic waste, and other tributary. The sensitivity analysis resu/Jed that the degrcukuion coefficient (k) was the most influential porameter tJ> the model concentratinn with sensitivity coefficient (S) = 0.311. 17re simulation resu/1$ for calibration with kCOD=O, 1 /day showed the model concentration was quite closed to the observed concentration in calibration and validation. The Cr simtdation for k = 3xl04 /sec resulted thor the model concentralion was quite valid to approach observed Cr in obsen•ation and calibration. Simulation result of plugflow for Cr showed thor kd1e0.12 nl!g was less close to tire observed Cr in calibration than advection-disperse model